Facile synthesis of a CoFe2O4-dopes tin disulfide in reduced graphene oxide matrix as anode material for lithium ion batteries - Salvador, Ruben W. Jr.; De Luna, Mark Daniel G.; Doong, Ruey-An (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Energy storage devices, such as Lithium Ion batteries, have been a vital apparatus in the modern era due to its use in Renewable Energy power production and various mobile and handheld devices. Thus there is a need to improve the current commercial graphite Lithium Ion batteries to keep up with the modern technological advances. SnS2 has taken an interest as anode material for Lithium Ion Batteries due to its high theoretical capacity. Integrating it into a graphene matrix further improves its performance due to an increase in structural stability and providing ease of intercalation of Lithium Ions. In this study, a facile and scalable integration of SnS2 hexagonal nanoplates into the reduced Graphene Oxide (rGO) have been successfully established by comparing three different methodologies. Among these three, the Hydrothermal Reduction method has been identified as the best performing anode material for Lithium ion batteries. Subsequently, CoFe2O4 has been successfully doped into the SnS2/rGO nanocomposite via the same method. The synergistic effect between the three components results in a successful CoFe2O4-doped, SnS2/rGO nanocomposite with high initial specific capacity of around 1700 mAh g-1, and reliable cycling performance of 430 mAh g» at 500 mA g-1 after 100 cycles. This active material showed better performance than the bare SnS2 and un-doped SnSz/rGO nanocomposite.
Thesis (Master of Science in Energy Engineering)--University of the Philippines Diliman
Keywords: Lithium ion batteries; Anodes